An Analysis of Socio-Economic Impacts of Trans Sumatera Pekanbaru- Dumai Toll Road Development - Hardika, Suci Atma; Aridianto, Jeki (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
ABSTRACT: The road network is one of success supporting factors of a development, so that it takes adequate road network and prioritize speed. By this development, there will be changes in the economic and social condition of society. This research aims to determine the impact of Trans Sumatera toll road Pekanbaru-Dumai construction to the socio-Economic community of Harapan Baru Village, Mandau Sub District, Bengkalis Regency. This type of research is quantitative descriptive. The population and sample of this research is a society that is close to the construction of the toll in the village of Harapan Baru namely RT. 002 and RT. 005. The Technique of the Data collections through interviews, observations, and polls. The result of the research is the construction of Trans Pekanbaru toll Road-Dumai resulted in positive and negative impacts. The positive impact is to open opportunities for business people around toll road construction and can reduce the number of unemployment in the village of Harapan Baru because of community involvement in the development, but not all communities in the region are working in the construction of the toll road, while the negative impact of toll road construction leads to the income of the plantation communities decreased due to reduced plantations. Keywords: impact, economy, toll road, development, social